Analisis Tren dan Perbandingan CAR, NPF, Pemenuhan PPAP, ROA, BOPO, Cash Ratio, dan FDR Pada Bank Syariah Mandiri dan Bank Muamalat Periode Desember 2004 Sampai Dengan Desember 2013 - Archelia Imarvianti; Dina Fitrisia Septiarini (Universitas Airlangga, 2015)
This research is to know the trend and the differences of financial performance between Bank Syariah Mandiri and Bank Muamalat in the periods of 2004-2013. This research used quantitative for the research method, purposive sampling for the sampling technique, Bank Syariah Mandiri and Bank Muamalat for the sample. This research conduct the trend analyzed,and conduct the comparative analyzed with independent sample t-test. This research used seven variables to evaluate the financial performance which was CAR, NPF, the fulfillment of PPAP, ROA, BOPO, cash ratio, and FDR.The trend analysis showed that Bank Syariah Mandiri has better progress on CAR, BOPO, cash ratio, and FDR, whereas Bank Muamalat has better progress on NPF, the fulfillment of PPAP and ROA. The comparative analysis showed that there are no differences on BOPO and cash ratio, whereas there are differences on CAR, NPF, the fulfillment of PPAP, ROA, and FDR.